PENGARUH TANAMAN RUMPUT BEBEK (Lemna minor) TERHADAP PENURUNAN BOD DAN COD LIMBAH CAIR DOMESTIK - Endro, Sutrisno; Sri, Sumiyati (Universitas Diponegoro, 2010)
Domestic wastewater coming from household activities is an environmental problem that needs to be taken seriously. For it. appropriate alternative treatment is needed, both in terms of economic efficiency and the environment. As one attempts to solve is to take advantage of duckweed plants as a medium to improve the quality of the leachate is biologically or as bioakumulator substance - contaminants. This study aims to determine the effectiveness (efficiency) of duckweed plants (Lemna minor) in a decreasing concentration of BOD and COD of domestic wastewater. The method used is based on laboratory analysis of BOD and COD concentration in wastewater samples. The process was performed under a batch system by varying the concentration of waste (20%, 25%, 33% and 50%) and residence time in reactor (0,5,10,15,20) days. The result of such treatment from day 0 to day 20, there is the highest efficiency in treatment for BOD 78.26% at concentrations of 50% and the COD is 71.15% at a concentration of 20%.